Efektifitas Strategi Pemasaran Produk Wisata Minat Khusus Gua Cerme, Imogiri, Bantul - Cahya Purnomo (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2008)
This research is aimed to recognize the marketing strategy for special interest tourism product of Cerme Cave located in Imogiri Subdistrict, Bantul Regency. The method used in this research is a descriptive survey method. Purposive sampling is used to determine sample. Findings found that the market characteristics of the respondens are young men, well educated, like to do adventure people, unemployment, group visitors; spend less expenditure and local people. Their main activities are tracing along the cave and doing the relaxation. The marketing strategy is recommended with 7P.Keyword: karakteristik pasar, kualitas produk, strategi marketing, stakeholders, gua cerme, Bantul